2014
DOI: 10.5966/sctm.2013-0149
|View full text |Cite
|
Sign up to set email alerts
|

Increased Genomic Integrity of an Improved Protein-Based Mouse Induced Pluripotent Stem Cell Method Compared With Current Viral-Induced Strategies

Abstract: It has recently been shown that genomic integrity (with respect to copy number variants [CNVs]) is compromised in human induced pluripotent stem cells (iPSCs) generated by viral-based ectopic expression of specific transcription factors (e.g., Oct4, Sox2, Klf4, and c-Myc). However, it is unclear how different methods for iPSC generation compare with one another with respect to CNV formation. Because array-based methods remain the gold standard for detecting unbalanced structural variants (i.e., CNVs), we have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 35 publications
1
14
0
Order By: Relevance
“…The corresponding figure for cytogenetic aberrations in our lines reprogrammed by SeV was 1 out of 16 and clearly below the reported average for iPSC using integrative methods. Furthermore, the rate of cytogenetic aberrations at early passages and after reprogramming with SeV in our study is in line with studies using episomal-based reprogramming [16]. After prolonged culture, we detected one acquired aberration in a SeV-reprogrammed line.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The corresponding figure for cytogenetic aberrations in our lines reprogrammed by SeV was 1 out of 16 and clearly below the reported average for iPSC using integrative methods. Furthermore, the rate of cytogenetic aberrations at early passages and after reprogramming with SeV in our study is in line with studies using episomal-based reprogramming [16]. After prolonged culture, we detected one acquired aberration in a SeV-reprogrammed line.…”
Section: Discussionsupporting
confidence: 92%
“…The reason for differences in the types of karyotypic abnormalities in iPSC versus ESC is yet unclear and it may be hypothesized that it is related to the methods used for reprogramming [15]. Furthermore, only a few studies have compared the frequency of genomic rearrangements in iPSC with respect to different methods of reprogramming [16]. The techniques for derivation of iPSCs can be broadly categorized into integrative and nonintegrative delivery of reprogramming factors.…”
Section: Introductionmentioning
confidence: 98%
“…To minimize the genomic instabilities of iPS cells, strategies of generating integration-free iPS cells have been developed. However, iPS cells generated either with episomal vector or protein-base method were still found to carry a large number of de novo genetic variants323. One of the most important reasons for the de novo genetic variants in iPS cells is that reprogramming process can trigger DNA damage response.…”
Section: Discussionmentioning
confidence: 99%
“…Relatively high expression of murine oct4 and sox2 genes in the group of iPSCs has been observed in this work, In the previous study, gene expression level was about 25-10 4 of murine oct4 and sox2 in a group of MEFs. 25,26 Our experimental results showed that a single MEFs achieved over 10 5 in gene expression level of murine oct4 and sox2, as shown in Table II. It also demonstrates that the application of the HDEN device achieved higher gene expression level in single host cell.…”
Section: Expression Of Ipsc Factor Genes Oskm In Mefsmentioning
confidence: 85%